Dinamika Dukungan Sosial dalam Kehidupan Sehari-Hari Lansia di Panti Jompo - Yuslih Maulida; Najwa Salsabil Bahri; Nur Aini Hidayah; Fikriyyah Maeyani; Bintang Dian Larasati; Indria adisti rahmadita; Asma'Nur Kamila; Faradila Chandra; Lufi Maulidta Wulanda; Siti Hikmah (Jurnal Kesehatan Amanah, 2025)
Elderly people living in nursing homes are vulnerable to limited social interaction and isolation, which impacts their psychological well-being and quality of life. Social support is an important factor in improving the well-being of the elderly in this environment. Therefore, this study aims to analyze the dynamics of social support received by the elderly in their daily lives at the Al-Hikmah nursing home, including the forms of support, the main sources of support, and the challenges faced. The study used a qualitative approach with 6 elderly participants aged 60-75 years who lived in nursing homes and were still able to communicate well. Data were collected through semi-structured interviews, then analyzed thematically. The results showed that the elderly received various forms of social support, namely emotional support, appreciation, instrumental, infor mation, and social networks. Emotional and instrumental support were the most felt, while information support was the most limited. Social interaction and involvement in religious or social activities strengthen the support network, but there is variation in the level of involvement between individuals. Therefore, adequate and sustainable social support from family, nursing home administrators, and the community plays a very important role in improving the psychological well-being and quality of life of the elderly in nursing homes. It is important to create an environment that encourages communication, social participation, and appreciation of the needs of the elderly.